SDF-1 alleviates osteoarthritis by resolving mitochondrial dysfunction through the activation of the Sirt3/PGC-1α signalling pathway - Yanping Zhao; Dan Lin; Xiaoying Zhu; Jingyao Yan; Yan Liang; Yanli Wang; Tianqi Dai; Zhiyi Zhang; Shuya Wang (Arthritis Research & Therapy)
Abstract Objective Osteoarthritis (OA) is the most common form of joint disease. Currently, OA treatment is limited to controlling symptoms. Our previous study showed that stromal cell-derived factor 1 (SDF-1) delayed the progression of OA to a certain extent. The aim of this study was to explore the specific mechanism of SDF-1 in OA. Materials and methods OA chondrocytes and a collagen-induced osteoarthritis (CIOA) mouse model were used as in vitro and in vivo models, respectively. SDF-1 was used to treat OA in vitro and in vivo. To explore the mechanism of SDF-1 in OA treatment, we pretreated chondrocytes with a Sirt 3 inhibitor and assessed mitochondrial function and then analysed related indicators of cartilage anabolic and cartilage metabolism. Results SOD2 and PGC-1α levels were significantly lower in OA chondrocytes and the cartilage of CIOA model mice than in normal chondrocytes, and mitochondrial dysfunction occurred in OA. After treating OA chondrocytes and CIOA model mice with exogenous SDF-1, mitochondrial dysfunction and abnormal biomarkers of OA normalized. The pretreatment of OA chondrocytes with a Sirt 3 inhibitor or mitochondrial function inhibitor before SDF-1 exposure reversed these changes. Conclusions SDF-1 can alleviate OA by resolving mitochondrial dysfunction through the activation of the Sirt3/PGC-1α signalling pathway, and therefore, SDF-1 may be a good candidate as a new treatment for OA.